2001
DOI: 10.1152/ajpregu.2001.281.1.r66
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular monocyte and serum cytokine expression is modulated by exhausting exercise and cold exposure

Abstract: This study tested the hypothesis that exercise elicits monocytic cytokine expression and that prolonged cold exposure modulates such responses. Nine men (age, 24.6 +/- 3.8 y; VO(2 peak), 56.8 +/- 5.6 ml. kg(-1). min(-1)) completed 7 days of exhausting exercise (aerobic, anaerobic, resistive) and underwent three cold, wet exposures (CW). CW trials comprised Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 55 publications
11
86
2
3
Order By: Relevance
“…A very low-CHO diet implies a very high-fat dietary content, which has been shown detrimental to immune function. We expected to find an increase in IL-6 from baseline following exercise in both dietary conditions, as previously reported in measurements taken after light, moderate and hard intensity exercise performed for short-and long-periods of time [2,7,12,22,27,34,40,51]. In our study, IL-6 increased significantly from baseline immediately following the duathlon regardless of the diet, and remained elevated 1-and 2-h following exercise.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A very low-CHO diet implies a very high-fat dietary content, which has been shown detrimental to immune function. We expected to find an increase in IL-6 from baseline following exercise in both dietary conditions, as previously reported in measurements taken after light, moderate and hard intensity exercise performed for short-and long-periods of time [2,7,12,22,27,34,40,51]. In our study, IL-6 increased significantly from baseline immediately following the duathlon regardless of the diet, and remained elevated 1-and 2-h following exercise.…”
Section: Discussionsupporting
confidence: 85%
“…3b). Mild-endotoxemia, defined as LPS-LBP complex > 5 pg/ml [51], was found at baseline in three participants (27%) on the low-CHO diet compared to only one (9%) participant on the high-CHO diet. However, endotoxemia was observed in six subjects (55%) immediately following exercise in the low-CHO diet, compared to five subjects (45%) on the high-CHO diet.…”
Section: Endotoxin and Il-6 Markers Regardless Of The Dietary Manipumentioning
confidence: 98%
“…A common finding when examining intracellular cytokine profiles with exercise, with or without hyperthermia, has been either no change or a slight reduction in the level of spontaneous TNF-␣ in cytokine-positive peripheral blood monocytes in trained (74,77,89) and untrained subjects (84), similar to the present study's responses in CD14 ϩϩ CD16 Ϫ monocytes. By contrast, Rhind et al (58) found corresponding increases in intracellular monocytic expression and circulating TNF-␣ during exhaustive exercise and subsequent cold exposure, changes that were suggested to be reflective of the inflammatory status of the cells before the exposure, or perhaps specific immune modulating influences accompanying exercise (58).…”
Section: Discussionmentioning
confidence: 92%
“…Many studies have reported changes in circulating proinflammatory cytokines during EHS (54,59,76), and the potential that these mediators originate from circulating leukocytes has been under considerable debate (21, 47, 58, 74 -76, 83). Several studies have examined monocytic protein content using a variety of methods including mRNA transcript expression (47, 83) and intracellular flow cytometry (58,74,76,77,84,89) in circulating monocytes, without distinction between subsets (21). We recently reported that increases in circulating TNF-␣ and endotoxin during EHS are accompanied by nuclear factor (NF)-B translocation in peripheral blood mononuclear cells, suggestive of peripheral blood inflammatory cell activation (68).…”
mentioning
confidence: 99%
“…The response of the body to cold temperatures occurs through changes in the endocrine system (increase in adrenocorticotropin concentration, β-endorphins, epinephrine, norepinephrine and testosterone concentration in men) [1][2][3][4], circulatory system (contraction of blood vessels in the skin, then their dilation and congestion of the skin) [5], neuromuscular system (reduction of muscle tension, decrease in nerve conduction velocity) [6] and immunological system (increase in cell-mediated and humoral immunity) [1,[7][8][9][10]. Moreover, whole body cooling influences the prooxidant-antioxidant balance in blood [11][12][13][14], and has an anti-inflammatory [15] as well as an analgesic effect [6].…”
Section: Introductionmentioning
confidence: 99%